2013
DOI: 10.3390/pharmacy1020137
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning: Reflections on Teaching Experiences across the Pharmacy Education Continuum

Abstract: Abstract:Experiences with online learning in higher education have grown due to advancements in technology, technological savviness of students, changes in student expectations, and evolution of teaching approaches in higher education. Blended learning, the thoughtful fusion of face-to-face instruction with online learning, can enhance student learning and provide rewarding teaching experiences for faculty members. Pharmacy educators are beginning to employ blended learning across the continuum of professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Blended learning supports the ability to have some face-to-face learning, along with some self-directed study. There are challenges when introducing blended learning, as complex planning, time, and resources are required, but there are multiple opportunities with this approach [ 39 ]. A study from pharmacists in the Middle East showed that whilst pharmacists appreciated the ability of online learning to be flexible, the challenges they faced included technology, time management, and learner isolation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blended learning supports the ability to have some face-to-face learning, along with some self-directed study. There are challenges when introducing blended learning, as complex planning, time, and resources are required, but there are multiple opportunities with this approach [ 39 ]. A study from pharmacists in the Middle East showed that whilst pharmacists appreciated the ability of online learning to be flexible, the challenges they faced included technology, time management, and learner isolation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2] To overcome these issues, educational researchers have come up with an amalgamation of the traditional and modern teaching methodologies which led to the concept of blended learning. [256] Blended learning has been used widely in many medical and dental subjects. [78] Literature review by Rowe suggested that blended learning has a potential to improve clinical competencies among health-care students and they find it intellectually stimulating.…”
Section: Discussionmentioning
confidence: 99%
“…Educational outcomes for the PharmD program include reflective practice and metacognitive skills, that is, the ability to reflect on knowledge, skills, and beliefs that could influence self-development and professional performance [30]. Reflection on teaching approaches (see Schindel et al [31]) and reflection on learning (see Nagy et al [32]) are both important. Students are introduced to the theoretical foundations of reflection in year 1 of the program and are required to complete a variety of reflective activities, such as written reflections and group discussions, in conjunction with in-class courses, practice skills laboratories, and experiential education placements.…”
Section: Educational Settingmentioning
confidence: 99%